Development of the Metaverse and learning - Alhakimi, Hanan (Universitas Sebelas Maret, 2023)
The metaverse is a shared virtual space that allows users to interact with each other and a variety of digital media. It has been shaped by technological advances, including the growth of the Internet, the development of virtual and augmented reality technologies, and the increasing power and capabilities of computers and mobile devices. The main goal of the metaverse is to create a seamless and immersive experience for users, allowing them to interact with each other and with digital media in a natural and intuitive way. The metaverse has the ability to provide new opportunities for entertainment, education and communication, and we can expect to see continuous development and innovation in this field in the future. This field aims to develop the field of education in all schools around the world. The declaration of the COVID-19 pandemic forced humanity to rethink how we teach and learn. The metaverse, a 3D digital space mixed with the real world and the virtual world, has been heralded as a trend of future education with great potential. However, as an emerging item, rarely did the existing study discuss the metaverse from the perspective of education. In this paper, we first introduce the visions of the metaverse, including its origin, definitions, and shared features